Penundaan Menikah pada Generasi Z: Perspektif Hukum Keluarga Islam dan Maqasid Syariah Jasser Auda - Kanza Indah Safitri; Jayusman; Linda Firdawaty; Amin Nugrah Santoso (SAKALIMA: Pilar Pemberdayaan Masyarakat Pendidikan, 2026)
The postponement of marriage among Muslim Generation Z has become a prominent socio-legal phenomenon shaped by economic uncertainty, educational aspirations, career orientation, digital culture, and changing perceptions of marital readiness. This article aims to analyze the factors that encourage Muslim Generation Z to delay marriage and to examine this phenomenon from the perspective of Islamic family law and Jasser Auda’s maqasid shariah systems approach. This study employs normative juridical research using conceptual and statutory approaches. The primary legal materials consist of Indonesian marriage regulations, the Compilation of Islamic Law, and Islamic legal principles related to marriage, while secondary materials include peer-reviewed journal articles, books, statistical reports, and contemporary studies on waithood, marriage anxiety, and Muslim youth. The materials were collected through a documented library search, selected based on relevance, recency, accessibility, and legal-conceptual suitability, and then analyzed using descriptive-analytical and prescriptive legal reasoning. The findings show that the postponement of marriage among Muslim Generation Z is mainly influenced by financial instability, educational and career priorities, psychological readiness, changing gender expectations, and digital narratives about family life. From the perspective of Islamic family law, marriage delay cannot automatically be regarded as a rejection of marriage; rather, it may be understood as an effort to achieve istitha‘ah and to prepare physical, psychological, economic, and spiritual readiness for responsible family life. Through Jasser Auda’s systems approach, the phenomenon can be read contextually through the features of cognition, wholeness, openness, interrelated hierarchy, multidimensionality, and purposefulness, all of which emphasize the protection of the self, lineage, dignity, and family welfare. The study implies that Islamic family law discourse needs to respond to Generation Z’s marital concerns through adaptive premarital education, family counseling, and contextual legal interpretation while maintaining the normative objectives of marriage in Islam.